FMCW multiple-input multiple-output radar with iterative adaptive beamforming - Eckhardt, Johannes M; Joram, Niko; Figueroa, Adrian; Lindner, Bastian; Ellinger, Frank (IET radar, sonar & navigation, 2018)
This work presents the design of a frequency modulated continuous wave (FMCW) multiple-input multiple-output radar system with collocated antennas. A key part of this article is the modification and application of the iterative adaptive algorithm (IAA) for digital beamforming to an FMCW radar system. The implemented system operates in the 2.4 GHz Industry, Scientific and Medical band with 100 MHz of bandwidth and consists of a transmit (TX) site with four antennas and a receive (RX) site with four antennas. The angular resolution is greatly improved from 15° with the common delay-and-sum beamforming to only 5° with IAA beamforming, which was verified by the results from a radar simulator and by a field test with the implemented hardware. The challenge of synchronisation and maintaining phase coherence in systems with remote TX and RX sites is also addressed by proposing a low-frequency clock and trigger distribution system. This approach allows for cost-efficient systems which can be distributed over longer distances.